Ensemble Hydrometeorological Forecasts Using WRF Hourly QPF and TopModel for a Middle Watershed. (14th May 2014) - Calvetti, Leonardo; Pereira Filho, Augusto José
Abstract : Quantitative precipitation forecasts (QPFs) were obtained from ensembles of the weather and research forecasting (WRF) model for the Iguaçu river watershed (IRW) in southern Brazil. Thirty-two rainfall events between 2005 and 2010 were simulated with ten configurations of WRF. These rainfall events range from local to synoptic scale convection and caused a significant increase in the level of the Iguaçu river. In the average, the ensembles yielded up to 20% better skill than single WRF forecasts for the events analyzed. WRF ensembles also allow estimating the predictability through the dispersion of the forecasts providing relevant information for decision-making. Phase errors of ensemble forecasts are larger than amplitude errors. More complex microphysics parameterizations yielded better QPFs with smaller phase errors. QPFs were fed to IRW hydrological model with similar phase and amplitude errors. It is suggested that lagged QPFs might reduce phase errors.